2017
DOI: 10.4172/2151-6200.1000309
|View full text |Cite
|
Sign up to set email alerts
|

Content Analysis of News Reporting about Women in the Kashmir Daily ‘Greater Kashmir’

Abstract: The print media including the regional newspapers are relied upon by the people as credible sources of information, education and entertainment. Various studies on print media all across the globe have shown that in the past few years there has been an improved and increased reportage of issues regarding women in the media particularly in the print. News related to women is now increasingly occupying important slot. Based on a content analysis of an English daily newspaper, Greater Kashmir, this paper examines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…Kashmiri women's testimonies-based report revealed that security forces targeted women because of their support of the freedom struggle and to break the movement itself (Maqbool, 2017). Khan (2017) studied violence against women in Kashmir as reported by the "Greater Kashmir" (Kashmir edition), a newspaper of J&K. According to the newspaper, around 81 women committed suicide or attempted to commit suicide. 16 cases of rape and molestation, one case of acid attack, and seven murders were reported from mid-2014 until the end of 2016.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kashmiri women's testimonies-based report revealed that security forces targeted women because of their support of the freedom struggle and to break the movement itself (Maqbool, 2017). Khan (2017) studied violence against women in Kashmir as reported by the "Greater Kashmir" (Kashmir edition), a newspaper of J&K. According to the newspaper, around 81 women committed suicide or attempted to commit suicide. 16 cases of rape and molestation, one case of acid attack, and seven murders were reported from mid-2014 until the end of 2016.…”
Section: Literature Reviewmentioning
confidence: 99%